Efforts to Improve the Development of Early Childhood Cognitive Ability in Kindergarten Ade Irma Mataloko - Vensensiana Nosi; Nurtiana Enem; Restina Go’o; Maria Rosalina Bhubhu; Felomena Sari Janul; Yuliana Mbadu; Maria Enjela Mola (PT FORMOSA CENDEKIA GLOBAL, 2023)
The practice activity of the teaching experience is a practice activity wherestudents train to become actual teachers. This is one of the most exciting activities because whenwe apply for the practice of teaching at the school the teacher will surely give us a full opportunity which means they give us the opportunity to teach the children. This teaching activity aims: (1) knowing the learning media design to increase children's cognitive cognitive at TKK ade Irma mataloko, (2) produces media that is practical to enhance children's cognitive abilities in TKK ade Irma mataloko. The recommendation of this research is that teachers are expected to consider implementing the methods of projects using the surroundings as alternative learning strategies especially in improving the children's cognitive in TK ADE MATALOKO.